User Payments for Basic Education in Low-Income Countries - Jenkner, Eva (IMF Working Papers; Working Paper, 2002)
Insufficient resources and inadequate public expenditure management often prevent governments in low-income countries from providing quality basic education free of charge. User payments by parents are an alternative means of financing basic education. This paper assesses how user payments affect educational opportunities and quality of education for children of poor families in low-income countries. Conditions are identified under which user payments can or cannot improve educational outcomes. User payments, whether taking the form of compulsory benefit taxation or voluntary user fees, are a temporary solution and second-best compared with free-access, publicly financed quality education that is consistent with macroeconomic stability.